The Corporate Social Performance of Developing Country Multinationals - Zyglidopoulos, Stelios C.; Williamson, Peter James; Symeou, Pavlos C. (My University, 2016)
In this article, we explore the Corporate Social Performance (CSP) of Developing Country Multinationals (DMNCs). We argue that in competing internationally, DMNCs often face both reputation and legitimacy deficits, which they address by improving their CSP. We develop a series of hypotheses to explain the variation in CSP between DMNCs and domestic-only firms from developing countries and also examine variations in CSP between DMNCs depending on the extent of their multinationality and portfolio of host countries. Our findings support all our hypotheses, which suggest that DMNCs display enhanced levels of CSP compared to their domestic-only counterparts. CSP is also found to be positively related to the DMNCs' degree of multinationality, but with a declining incremental impact, whereas entry into developed markets leads to a greater improvement in DMNCs' CSP than expansion into developing markets. We highlight the implications of our findings for managers and researchers.
Keywords: Corporate Social Performance; Developing Country Multinationals